Chemotaxonomy of Mycotoxigenic Small-Spored Alternaria Fungi – Do Multitoxin Mixtures Act as an Indicator for Species Differentiation? - Zwickel, Theresa; Kahl, Sandra M.; Rychlik, Michael; Müller, Marina E. H. (Frontiers in Microbiology, 2018)
Necrotrophic as well as saprophytic small-spored Alternaria (A.) species are annually responsible for major losses of agricultural products, such as cereal crops, associated with the contamination of food and feedstuff with potential health-endangering Alternaria toxins. Knowledge of the metabolic capabilities of different species-groups to form mycotoxins is of importance for a reliable risk assessment. 93 Alternaria strains belonging to the four species groups A. tenuissima, A. arborescens, A. alternata and A. infectoria were isolated from winter wheat kernels harvested from fields in Germany and Russia and incubated under equal conditions. Chemical analysis by means of a HPLC-MS/MS Multi-Alternaria-toxin-method showed that 95% of all strains were able to form at least one of the targeted 17 Alternaria toxins. Simultaneous production of up to 15 (modified) Alternaria toxins by members of the A. tenuissima, A. arborescens, A. alternata species-group and up to 7 toxins by A. infectoria strains was demonstrated. Overall tenuazonic acid was the most extensively formed mycotoxin followed by alternariol and alternariol mono-methyl ether, whereas altertoxin I was the most frequently detected toxin. Sulfoconjugated modifications of alternariol, alternariol mono-methyl ether, altenuisol and altenuene were frequently determined. Unknown perylene quinone derivatives were additionally detected. Strains of the species-group A. infectoria could be segregated from strains of the other three species-groups due to a significantly lower toxin levels and the specific production of infectopyrone. Apart from infectopyrone, alterperylenol was also frequently produced by 95% of the A. infectoria strains. Neither by the concentration nor by the composition of the targeted Alternaria toxins a differentiation between the species groups A. alternata, A. tenuissima and A. arborescens was possible.